Performance analysis of 5G path loss models for rural macrocell environment - Mohd Nordin, Muhammad Akramuddin; Mohd Ramli, Huda Adibah (IIUM Press, 2020)
5G networks are expected to use the Millimeter Wave (mmWave) frequency band and this frequency provides wider bandwidth allowing a better quality of service to be offered to the users. However, the mmWave frequencies may lead to a higher path loss due to several factors including blockages,rain and atmosphere. Therefore, to allow optimal positioning of the 5G base stations, the study of path loss model in this 5G mmWave frequencies is crucial. This paper investigates the 5G path loss models as well as their parameters that are most suitable for cross-polarized antennas under rural macrocell environment in Malaysia. Path loss models namely Close In Free Space Reference Distance Path Loss Model (CI) model, and Alpha Beta Gamma (ABG) or Floating Intercept (FI) Model along with their parameters achieved from the previous studies were evaluated by comparing the parameters and models that are closest to the sampled path loss when using antennas that have different patterns and polarizations in an open-source simulator. Results obtained indicate that FI model can be adapted to the majority of the environment where this model showed the lowest Root Mean Square Error (RMSE). The study of path loss models by using advanced simulator or field measurement, and studies on other rural areas from other states in Malaysia will be considered in future works.